Zenith of Intensity Batsheva Dance Theatre - Felsenburg, Ben (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Ohad Naharin is an Israeli contemporary dancer and choreographer. He served as artistic director of Batsheva Dance Company from 1990 to 2017. Naharin needs his dancers' individual humanity, not just their honed technique.